Contribution of grain size to resistance against cleavage crack propagation in ferritic steel. (15th September 2019) - Yanagimoto, Fuminori; Hemmi, Takuhiro; Suzuki, Yuta; Takashima, Yasuhito; Kawabata, Tomoya; Shibanuma, Kazuki
Abstract: This study investigates the contribution of grain size to cleavage crack propagation resistance in ferritic steels. A series of crack arrest tests were conducted using three kinds of steel, which had the same chemical composition but different grain sizes. Dynamic finite element analyses were used to simulate the respective crack arrest tests in order to evaluate local fracture stress. The results clearly showed that coarse-grained steel has higher local fracture stress. These results showed the opposite tendency to the well-known dependence of cleavage fracture initiation resistance on grain size. To understand these results from a micromechanics viewpoint, the energy dissipation during cleavage crack propagation was evaluated based on the consumed energy in the tear-ridge formation. Small-scale tensile experiments simulating tear-ridge formations were conducted using specimens with a pair of focused-ion-beam-machined slit-notches to simulate cleavage planes. The energy consumed during tear-ridge formation was quantified as a function of the cleavage plane distance based on the results of small-scale tests. Combining the quantified experimental results with the cleavage crack propagation model based on the extended finite element method, the energy dissipation in steels with various grain sizes was evaluated. The energy dissipation results showed the same tendency as the local fracture stress results. In other words, higher resistance against cleavage crack propagation can be obtained in coarse-grained steel. Graphical abstract: Image 1